Forest genetics research in the Mediterranean Basin: Bibliometric analysis, knowledge gaps, and perspectives - Fady, Bruno; Ivetic, Vladan; Esposito, Edoardo; Aleksic, Jelena M.; Alia, Ricardo; Alizoti, Paraskevi; Apostol, Ecaterina-Nicoleta; Aravanopoulos, Phil; Ballian, Dalibor; Dagher Kharrat, Magda Bou; Carrasquinho, Isabel; Cheikh Albassatneh, Marwan; et al. (Springer, 2022)
Purpose of Review Recognizing that in the context of global change, tree genetic diversity represents a crucial resource for future forest adaptation, we review and highlight the major forest genetics research achievements of the past decades in biodiversity-rich countries of the Mediterranean region. For this, we conducted a bibliometric analysis of the scientific literature spanning the past thirty years (1991–2020). Putting together the representative regionwide expertise of our co-authorship, we propose research perspectives for the next decade.